Pendampingan Pengembangan Profesional Guru PAI Berbasis Nilai Kejujuran dan Keteladanan di SDN Kemiri Sewu 1 Pandaan, Pasuruan - Abdul Mukhlis; Anhar, Ahmad Bahrurizqi; Ahmad Suyuti; Afni Fina Afifah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This community service program aimed to develop the professionalism of Islamic Religious Education (PAI) teachers through mentoring based on the values of honesty and exemplary conduct at SDN Kemiri Sewu 1 Pandaan, Pasuruan. The background of this activity stems from the weak internalization of honesty values in PAI learning practices and the need for a teacher development model that systematically integrates moral and spiritual dimensions. The program employed a qualitative approach with a participatory case study design, encompassing stages of needs assessment, reflective training, value-based microteaching, and collaborative evaluation. The results show a significant improvement in teachers’ ethical and professional awareness, as indicated by consistent honesty, openness in reflection, and their ability to model moral integrity within the school environment. Religious habituation activities such as congregational dhuha prayer, Qur’anic recitation, and daily prayers effectively internalized honesty as a form of spiritual consciousness. This program contributes to strengthening PAI teachers’ professionalism and fostering a character-based school culture, recommending the development of a sustainable mentoring model grounded in honesty and exemplary conduct as a strategic framework for Islamic teacher professional development at the elementary school level.